COMPUTATIONAL THINKING INSTRUMENTS AS A PROBLEM-SOLVING METHOD IN OBJECT-ORIENTED PROGRAMMING MATERIALS IN VOCATIONAL SCHOOLS - Eka Fitrajaya Rahman; Dwi Fitria Al Husaeni; Erna Piantari (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2023)
This study aims to develop a Computational Thinking (CT) instrument on Object-Oriented Programming material as a tool for measuring the level of CT in the problem-solving abilities of Vocational High School students. The Plomp model of R&D analysis is used as a research flow. There are four stages of CT instrument development, namely 1) preliminary investigation stage, 2) design stage, 3) realization stage, and 4) evaluation stage. The research method uses a quantitative approach with statistical analysis. The research subjects were 35 Grade 10 students at SMK Negeri 11 Bandung. The findings show that PBO material is suitable for use as a medium for developing CT instruments. Based on the results of the material expert validation and the instrument showed very good results. The instruments developed have been tested for validity, reliability, level of difficulty, and discriminatory power. There were 80 out of 100 questions which were declared valid and reliable for use. The difficulty level of the instrument is in the easy category (46 questions) and medium (54 questions). Meanwhile, the differentiating power of the instrument was in the range of sufficient (17 questions), good (57 questions), and very good (10 questions). The CT instrument developed in this study has categories of 24 abstraction questions, 20 pattern recognition questions, 18 decomposition questions, and 18 algorithm design questions. With the completion of this instrument, it is hoped that it can assist teachers or researchers in measuring problem-solving abilities, especially students' CT abilities.